Psychological Resilience: Does It Affect Students' Psychological Well-Being and Mental Health? - Diana Vidya Fakhriyani (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2025)
Recently, there has been growing attention to students’ mental health and psychological well-being as they face increasing academic and social pressures. Many students face emotional challenges, making it crucial to investigate whether psychological resilience can serve as a protective factor for their well-being and mental health.The present study aims to explore the impact of psychological resilience on students’ mental health and psychological well-being. This research employs a literature review method, in which the researcher systematically examines scientific sources such as journal articles, books, and other relevant publications related to psychological resilience and mental health. According to research findings, psychological resilience is crucial for psychological well-being and mental health. Students that possess strong psychological resilience are more capable of handling stress, adjusting to changes, recovering from setbacks, and exhibiting improved psychological health and a decreased likelihood of psychological diseases. These findings highlight the importance of nurturing psychological resilience, particularly among students, as a key element in promoting mental health and achieving psychological well-being.